ANALISIS EFEKTIVITAS PERPUTARAN MODAL KERJA PADA PROFITABILITAS CV. PURNAMA - Ramadhani, Maghfirah; Nasution, Ute Ch; Pratiwi, Ni Made Ida (Jurnal Dinamika Administrasi Bisnis, 2019)
This study aims to determine whether the effectiveness of the use of working capital on CV Purnama can increase profitability. The research method used in this study is a quantitative research method, with the aim of testing the predetermined hypothesis. The population in this study is a financial report in the form of a balance sheet and income statement of CV Purnama. The sampling in this study was to use CV Purnama's financial statements for the period 2015-2017. CV Purnama's return on assets in 2015-2017 be very volatile, in 2015 on aseet was high up to 11%. In 2016 CV Purnama's return on assets decreased to 6% due to the increase in assets which were increasingly not proportional to net income. In 2017 return on assets increased by 9%. Overall, Gross Profit Margin and Return on Equity ratio of the company is very good, because it increases every year. The effectiveness of the use of working capital can increase the profitability of the company, if the velocity of working capital of the return of capital turnover it works faster and fater.. Working capital turnover itself starts from when cash is invested in the component of working capital until it returns to cash, it means that the company's profitability has increased. Good management of working capital management where the effectiveness of working capital from 2015-2017 has increased so that the profitability of the company quickly and rose.Keywords: Effectiveness, Working Capital Turnover, Profitability